PELATIHAN MENULIS BAHASA INGGRIS EFEKTIF BERBASIS TEKNOLOGI DI LKP MUTIARA INFORMATIKA - Syahputra, Abdul Karim; Adimas, Adi Mas Afandi; Akmal, Akmal; Difki , Difki Putra Ramadhan (STMIK Royal, 2025)
Abstract: This training was organized to address the challenges faced by students at LKP Mutiara Informatika in Kisaran in producing coherent and accurate English writing. English writing skills are essential in the global era but are often hindered by limitations in grammar, vocabulary, and structure. This community service program aimed to enhance students' writing abilities through the utilization of Artificial Intelligence (AI). The training method included interactive sessions, demonstrations of popular AI tools (e.g., Grammarly, ChatGPT, and Gemini), and hands-on practice in composing paragraphs and essays. The results showed a significant improvement in the students' grammatical accuracy, vocabulary richness, and coherence. The training also boosted the participants' confidence in writing. Implicitly, this program contributes to workforce readiness and digital literacy, offering a training model that can be replicated in other institutions. However, ongoing challenges must be addressed, particularly the risk of over-reliance on AI and the importance of further training to preserve authenticity and critical thinking in writing. Keywords: artificial intelligence (AI); writing skills; english language Abstrak: Pelatihan diselenggarakan untuk mengatasi tantangan peserta didik LKP Mutiara Informatika di Kisaran dalam menghasilkan tulisan Bahasa Inggris yang koheren dan akurat. Keterampilan menulis Bahasa Inggris esensial di era global, namun seringkali terhambat oleh keterbatasan tata bahasa, kosakata, dan struktur. Kegiatan pengabdian masyarakat ini bertujuan meningkatkan kemampuan menulis peserta didik melalui pemanfaatan Kecerdasan Buatan (AI). Metode pelatihan meliputi sesi interaktif, demonstrasi penggunaan tools AI populer (misalnya, Grammarly, ChatGPT, dan Gemini), serta praktik langsung penyusunan paragraf dan esai. Hasilnya menunjukkan peningkatan signifikan pada akurasi tata bahasa, kekayaan kosakata, dan koherensi tulisan peserta didik. Pelatihan ini juga membangun kepercayaan diri peserta dalam menulis. Secara implisit, program ini berkontribusi pada kesiapan tenaga kerja dan penguasaan teknologi digital, serta menawarkan model pelatihan yang dapat direplikasi di institusi lain. Namun, tantangan berkelanjutan perlu diwaspadai, terutama risiko ketergantungan berlebih pada AI dan pentingnya pelatihan lanjutan untuk menjaga otentisitas dan pemikiran kritis dalam menulis. Kata kunci: kecerdasan buatan (AI); keterampilan menulis; bahasa inggris